Ischemia-Reperfusion under Hyperthermia Increases Heme Oxygenase-1 in Pyramidal Neurons and Astrocytes with Accelerating Neuronal Loss in Gerbil Hippocampus - Lee, Tae-Kyeong (Int J Mol Sci, 2021)
It has been studied that the damage or death of neurons in the hippocampus is different according to hippocampal subregions, cornu ammonis 1–3 (CA1–3), after transient ischemia in the forebrain, showing that pyramidal neurons located in the subfield CA1 (CA1) are most vulnerable to this ischemia. Hyperthermia is a proven risk factor for brain ischemia and can develop more severe and extensive brain damage related with mortality rate. It is well known that heme oxygenase-1 (HO-1) activity and expression is increased by various stimuli in the brain, including hyperthermia. HO-1 can be either protective or deleterious in the central nervous system, and its roles depend on the expression levels of enzymes. In this study, we investigated the effects of hyperthermia during ischemia on HO-1 expression and neuronal damage/death in the hippocampus to examine the relationship between HO-1 and neuronal damage/death following 5-min transient ischemia in the forebrain using gerbils. Gerbils were assigned to four groups: (1) sham-operated gerbils with normothermia (Normo + sham group); (2) ischemia-operated gerbils with normothermia (Normo + ischemia group); (3) sham-operated gerbils with hyperthermia (39.5 ± 0.2 °C) during ischemia (Hyper + sham group); and (4) ischemia-operated gerbils with hyperthermia during ischemia (Hyper + ischemia group). HO-1 expression levels in CA1–3 of the Hyper + ischemia group were significantly higher than those in the Normo + ischemia group. HO-1 immunoreactivity in the Hyper + ischemia group was significantly increased in pyramidal neurons and astrocytes with time after ischemia, and the immunoreactivity was significantly higher than that in the Normo + ischemia group. In the Normo + Ischemia group, neuronal death was shown in pyramidal neurons located only in CA1 at 5 days after ischemia. However, in the Hyper + ischemia group, pyramidal neuronal death occurred in CA1–3 at 2 days after ischemia. Taken together, our findings showed that brain ischemic insult during hyperthermic condition brings up earlier and severer neuronal damage/death in the hippocampus, showing that HO-1 expression in neurons and astrocytes is different according to brain subregions and temperature condition. Based on these findings, we suggest that hyperthermia in patients with ischemic stroke must be taken into the consideration in the therapy.